Parasitosis intestinales en niños y adolescentes de la etnia Yukpa de Toromo, estado Zulia, Venezuela. Comparación de los años 2002 y 2012 - Bracho M Angela; Rivero-Rodríguez Zulbey; Rios P Melary; Atencio T Ricardo; Villalobos P Rafael; Rodríguez Luis (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
Abstract: The prevalence of intestinal parasites in indigenous children and adolescents from Toromo, State of Zulia, was determined in 2012 and compared with the prevalence obtained in the same community in 2002. Both times, a stool sample was requested, which was subjected to a fresh coproparasitological examination with physiological saline and lugol, formalin-ether concentration and Kinyoun staining. The overall prevalence of intestinal parasites for the years 2002 and 2012 was 83.52% and 88.16%, respectively; protozoa prevailed over helminths. In both years, the species that occupied the first places were: Blastocystis spp. (51.65%/48.68%), Endolimax nana (37.36%/38.16%), Entamoeba coli, and helminths Ascaris lumbricoides (57.14%/63.16%), Trichuris trichiura (20.88%/23.68%) and Ancylostomideos (4.40%/23.68%). A statistically significant difference was observed in the prevalence of Iodamoeba butschlii, Strongyloides stercoralis and Ancylostomideos, when comparing the two dates. No intestinal coccidia were detected. Conclusions were that the maintenance and increase of intestinal parasites in individuals of the community is due to the lack of potable water, lack of environmental sanitation, poor education and cultural aspects of these indigenous people. Resumen: Se determinó la prevalencia de parásitos intestinales en niños y adolescentes indígenas de Toromo, Estado Zulia, en el año 2012 y a la vez se comparó con la obtenida en la misma comunidad en el año 2002. En ambas ocasiones, se solicitó una muestra fecal, la cual fue sometida al examen coproparasitológico al fresco con solución salina fisiológica y lugol, método de concentración de Formol-Éter y la coloración de Kinyoun. La prevalencia general de enteroparásitos para los años 2002 y 2012 fue de 83,52% y 88,16% respectivamente; donde prevalecieron los protozoarios sobre los helmintos. En ambos años, las especies que ocuparon los primeros lugares fueron: Blastocystis spp. (51,65%/48,68%), Endolimax nana (37,36%/38,16%), Entamoeba coli (36,26%/43,42%), y de los helmintos Ascaris lumbricoides (57,14%/63,16%), Trichuris trichiura (20,88%/23,68%) y Ancylostomideos (4,40%/23,68%). Se observó una diferencia estadísticamente significativa en la prevalencia de Iodamoeba butschlii, Ancylostomideos y Strongyloides stercoralis al comparar ambas fechas. No se detectaron coccidios intestinales. Se concluye que el mantenimiento y aumento de las parasitosis intestinales en los individuos de la comunidad, se debe a la carencia de sistemas de agua potable, falta de saneamiento ambiental, poca educación y aspectos culturales de estos indígenas.